Digital Educational Applications as Mediators of Cognitive and Social Development in Early Childhood Education - Ika Aizzatul Farida; Khotimatus Sholihah; Moh. Vito Miftahul Munif (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
The rapid integration of digital technology into early childhood education has created both opportunities and challenges regarding its influence on children's developmental outcomes. This study aims to examine how digital educational applications function as mediators of cognitive and social development in early childhood education and to explore the role of teacher guidance in facilitating meaningful technology-supported learning experiences. This research employed a qualitative case study design conducted at Bina Putra Kindergarten. Data were collected through classroom observations, semi-structured interviews with the school principal and teachers, and documentation. The collected data were analyzed using thematic analysis, while data credibility was ensured through source and method triangulation. The findings reveal that digital educational applications, including instructional videos, animations, and interactive learning platforms, support children's cognitive development by enhancing concentration, memory, symbolic recognition, conceptual understanding, and problem-solving abilities. Simultaneously, these applications contribute to social development by fostering cooperation, discipline, communication skills, patience, peer interaction, and collaborative learning behaviors. The findings further demonstrate that the developmental benefits of digital educational applications emerge not solely from technological features but from active teacher mediation, structured classroom interaction, and developmentally appropriate learning practices. The originality of this study lies in its conceptualization of digital educational applications as pedagogical mediators that simultaneously facilitate cognitive and social development rather than merely serving as instructional tools. This study contributes to the literature on early childhood education and digital pedagogy by proposing a teacher-guided digital mediation perspective that highlights the interconnected roles of technology, teacher facilitation, classroom culture, and children's active participation in supporting holistic child development.